2017
DOI: 10.1038/srep43372
|View full text |Cite
|
Sign up to set email alerts
|

Improved Bioavailability and Antitumor Effect of Docetaxel by TPGS Modified Proniosomes: In Vitro and In Vivo Evaluations

Abstract: A novel oral drug delivery system, TPGS modified docetaxel proniosomes (DTX-TPGS-PNs), was designed to enhance the oral bioavailability and antitumor efficiency of the poorly water-soluble drug docetaxel. DTX-TPGS-PN niosomes were 93 ± 6.5 nm in size, −18.53 ± 1.65 mV in zeta potential and exhibited spherical morphology, with an encapsulation efficiency of 97.31 ± 0.60%. The system showed sustained release in both simulated gastric and intestinal fluid. The results of caco-2 monolayer, everted gut sac model an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Lactate dehydrogenase is an intracellular enzyme, which can be used as an important indicator of membrane integrity [41]. When cell death occurs, large amounts of intracellular lactate dehydrogenase may be released into the media [42].…”
Section: Resultsmentioning
confidence: 99%
“…Lactate dehydrogenase is an intracellular enzyme, which can be used as an important indicator of membrane integrity [41]. When cell death occurs, large amounts of intracellular lactate dehydrogenase may be released into the media [42].…”
Section: Resultsmentioning
confidence: 99%
“…From the data, it was concluded that Vitamin E TPGS fabricated the emulsion with higher percentage transmittance as compared to others ( Table 7). The other surfactants tested for their emulsification ability were also successful in producing sufficiently good emulsion but TPGS was preferred over the others because of its benefits like anticancer activity which will provide a synergistic effect, nontoxicity, safety, biodegradability and antioxidant properties 30,[36][37][38][39][40] .…”
Section: Selection Of Surfactantmentioning
confidence: 99%
“…Oral pharmacokinetics showed a 7.3-fold improved absolute oral bioavailability compared to a DTX solution and significantly higher antitumor efficacy in MCF-7-bearing mouse model. 127…”
Section: Proniosomesmentioning
confidence: 99%